Effects of cooling vest and personal protective equipment removal on thermoregulation in wildland firefighters during progressive thermal loads - Gutiérrez-Arroyo, Jorge; Rodríguez-Marroyo, Jose A.; García-Heras, Fabio; Rodríguez-Medina, Juan; Collado, Pilar S.; Villa-Vicente, José G.; Carballo-Leyenda, Belén (Frontiers in Public Health, 2024)
Wildland firefighters (WFFs) regularly face demanding physical and environmental conditions during their duties, such as high ambient temperatures, challenging terrains, heavy equipment and protective gear. These conditions can strain thermoregulatory responses, leading to increased fatigue and posing risks to their health and safety. This study examined the effectiveness of two cooling interventions during physical activity in hot environments. Eight active male WFFs participated, comparing the effects of wearing a cooling vest (VEST) and personal protective equipment removal (PASSIVE) against a control condition (PPE). Participants walked on a treadmill at a speed of 6 km⋅h -1 for approximately 75-min under hot conditions (30°C and 30% relative humidity). Incremental slope increases were introduced every 15 min after the initial 20 min of activity, with 5-min passive recovery between each increment. Physiological and perceptual parameters were monitored throughout the protocol. Significant main effects (p<0.05) were observed in skin temperature (36.3 ± 0.2, 36.2 ± 0.4 and 35.4 ± 0.6 ºC in PPE, PASSIVE and VEST, respectively), physiological strain index (5.2 ± 0.4, 5.6 ± 1.1 and 4.3 ± 1.4 in PPE, PASSIVE and VEST) and thermal sensation (6.6 ± 0.6, 6.4 ± 0.7 and 5.3 ± 0.7 in PPE, PASSIVE and VEST). However, no significant effects of the cooling strategies were observed on heart rate, gastrointestinal temperature or performance. Despite the observed effects on physiological responses, neither cooling strategy effectively mitigated thermal strain in WFFs under the experimental conditions tested.